2014
DOI: 10.1039/c3cp53077a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical stability of non-aqueous electrolytes for sodium-ion batteries and their compatibility with Na0.7CoO2

Abstract: The present study compares the physico-chemical properties of non-aqueous liquid electrolytes based on NaPF6, NaClO4 and NaCF3SO3 salts in the binary mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC). The ionic conductivity of the electrolytes is determined as a function of salt concentration and temperature. It is found that the electrolytes containing NaClO4 and NaPF6 exhibit ionic conductivities ranging from 5 mS cm(-1) to 7 mS cm(-1) at ambient temperature. The electrochemical stability windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(164 citation statements)
references
References 72 publications
7
154
0
3
Order By: Relevance
“…2b, κ nearly exponentially decreases with the decrease of temperature. The measured values of κ, ∼9 mS cm −1 at room temperature, are somewhat higher than for traditional propylene carbonate and ethylene carbonate -dimethyl carbonate based Na-ion battery electrolytes [23][24][25][26] but somewhat lower Cyclic voltammetry data.-The cyclic voltammograms (CVs) were measured in two-electrode test cells at potential scan rate (ν) of 5 mV s −1 to establish the region of ideal polarizability of the C(Mo 2 C) electrodes in the tested electrolytes (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…2b, κ nearly exponentially decreases with the decrease of temperature. The measured values of κ, ∼9 mS cm −1 at room temperature, are somewhat higher than for traditional propylene carbonate and ethylene carbonate -dimethyl carbonate based Na-ion battery electrolytes [23][24][25][26] but somewhat lower Cyclic voltammetry data.-The cyclic voltammograms (CVs) were measured in two-electrode test cells at potential scan rate (ν) of 5 mV s −1 to establish the region of ideal polarizability of the C(Mo 2 C) electrodes in the tested electrolytes (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…266 Please do not adjust margins Please do not adjust margins Comparative studies were reported on electrolytes based on commercially available sodium salts, namely NaPF6, NaClO4 and NaCF3SO3 in a binary mixture of EC and DMC. 268 It was found that the ionic conductivity of the two solutions of 0.6 mol L ─1 NaPF6 and 1.0 mol L ─1 NaClO4 in EC and DMC were 6.8 and 5.0 mS cm ─1 , respectively. These values are somewhat higher than that of NaOTf (3.7 mS cm ─1 , 0.8 mol L ─1 ).…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…Unfortunately, NaOTf, NaFSI and NaTFSIbased electrolytes had the major drawback of being unable to form a passivation layer on the Al current collector. 268,269 A systematic evaluation of the intrinsic Al stability in electrolytes based on various NaX [X=PF6, ClO4, TFSI, FTFSI, FSI] salts dissolved in solvent mixtures showed a trend of the Al dissolution increasing in an order of NaPF6 < NaClO4 < NaTFSI < NaFTFSI < NaFSI. 270 When adding 5 wt.% NaPF6 to the base electrolyte, the stability of Al in imide-based electrolytes could be improved, which may be attributed to the formation of a protection passivation layer on the Al surface.…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…89 Bhide and Adelhelm et al proved the presence of NaF in NaPF 6 (99.0%, Alfa Aesar) using X-ray diffraction and the observation of the insoluble fraction in NaPF 6 /EC:DMC solution by eyes. 92 Detailed study on influence of impurities contained in NaPF 6 salts on sodium insertion properties is required for further understanding. Therefore, influence of the NaPF 6 salts with different purity on electrochemical properties has been investigated using the salts supplied different companies.…”
Section: Electrolyte Salts Solvents Additives and Bindersmentioning
confidence: 99%